Potential pitfall of local vegetable in Malaysia: Cytomorphological diagnosis interferences / Muhammad Harith Nor A’shimi - Nor A’shimi, Muhammad Harith (2015)
Introduction: Misdiagnosis of diseases are associated with pitfalls may contribute to false positive or false negative result which then whether will cause delays in diagnosis or an unnecessary treatment thus led to morbidity. This problem can affect the hospital budget because of delay in giving treatment and misdiagnosing. Pitfalls also occur from sample preparation until the screening of the slide. Food contaminants such as local vegetable can cause pitfall in diagnosis by mimicking the benign cell, malignant cell or the microorganism that related to human cells in cytology. Objective: The aim of this study is to describe morphologies of local vegetable cells, while to compare the morphological characteristics that have resemblances to malignant and normal cytology cells. Method: Local vegetables were crushed by using mortar and pestle, then smear on glass slides using 'pick and smear' method. Slides are stain with Papanicolaou stain and May Grunwald Giemsa stain. Result and Discussion: Vegetables cells contain nucleus, cytoplasm and cell walls. Some of selected local vegetable cells, such as long bean cell, lady's finger cell, luffa cell, bean sprout and chili can resemble squamous epithelial cell. Long bean cell also resemble fungal element while greater galangal cell can resemble parasitic ova. Besides that, water spinach cell resembles characteristic of AGe NOS and mustard green cell resemble Actinomyces spp. Conclusion: The characteristics of local vegetable cells resemble benign human cells and parasitic ova thus causing pitfalls in diagnosis. Therefore, this study can aid to minimize pitfall by making a catalogue of cytology diagnosis.